(untitled) (International Journal of Informatics, Information System and Computer Engineering (INJIISCOM), 2025)
The increasing interest in climate changes necessitates different effective solutions of data-driven decision-making in order to promote sustainability. In this paper, a proposed framework of data mart model designed to manage and analyze dataset of climate change in a station in Basrah, Iraq. The main aim is to examine the proposed data mart for support sustainable decisions by diving in different factors such as temperature, solar radiation, rain, wind speed at (10, 30, 50, 52) meters, wind direction, and humidity. The proposed schema for data mart is star schema to facilitate on-line analytical processing operations (roll up and drill down) through hierarchy of date, and for future advanced analytics. Power BI is used to design different dashboards to visualize data, and provide actionable insights for environmental researchers, decision makers, and stakeholders. The proposed model demonstrates real-time indicators and key performance indicators, with many customizable dashboards which ultimately provide stakeholders to make short-term decisions regarding climate change effects. The future works focus on integrating many other climate changes dataset from different locations and integrating predictive models of machine learning algorithms for forecasting patterns that support sustainability.